LAPORAN PENELITIAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA USAHA MIKRO KECIL MENENGAH (UMKM) TEH POCI MAK RAJE - Fiona Agnesia; Suci Febrianti; Salsa Herawati; Hadli Lidya Rikayana (Journal of Innovative and Creativity, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute the primary pillar of the Indonesian economy, significantly contributing to the Gross Domestic Product (GDP) and national employment. However, many MSMEs, exemplified by the Teh Poci Mak Raje unit, struggle with fundamental financial management issues. Their current system is often rudimentary, relying only on daily cash flow records and lacking formal financial statements compliant with accounting standards. This deficiency compromises the accurate calculation of net profit, hinders performance evaluation, and limits credibility for accessing formal financing. To bridge this gap, the Indonesian Accountants Association (IAI) issued the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in 2016, specifically designed to simplify the preparation of reliable and relevant financial statements for MSMEs. This study aims to determine the true financial condition of the Teh Poci Mak Raje MSME through the implementation of SAK EMKM. A descriptive qualitative and quantitative methodology was employed using a naturalistic approach. Data was collected via direct observation, in-depth interviews with the owner (Mrs. Eka), and documentation of transaction data. The findings demonstrate a successful transformation from simple record-keeping to formal financial reporting. The resultant reports for the 2025 period the Statement of Financial Position, Statement of Profit or Loss, and Notes to the Financial Statements (CALK) were compiled following a full accounting cycle, including journalizing, posting, and adjustments for depreciation and Cost of Goods Sold calculation. The research concludes that implementing SAK EMKM provides the MSME with a systematic, structured, and accurate financial overview. This is crucial for informed managerial decision-making and is vital for strengthening the competitiveness and long-term sustainability of MSMEs in the modern economic environment.